CO2 Enrichment Stimulates Dissolved Organic Carbon Release in Coral Reef Macroalgae. Issue 4 (22nd May 2020) - Diaz‐Pulido, Guillermo; Barrón, Cristina
Abstract : Dissolved organic carbon (DOC) released by macroalgae is important in the context of coral reef degradation as it contributes to coral mortality by promoting bacterial metabolism on the coral surface. Using experimental carbon dioxide (CO2 ) manipulations in outdoor flow‐through tanks, we found that seawater CO2 enrichment enhances daily net DOC release in a range of macroalgal species in the Great Barrier Reef (Australia). There was, however, large variability in DOC release among species, light and dark conditions, and CO2 exposure times. Under light conditions, DOC release in the red macroalga Amansia was 15 times higher under high CO2 conditions compared to ambient CO2, however, CO2 enhancement did not affect DOC production in the other species. Results from the night incubations were more consistent as three of the four species ( Amansia, Lobophora, and Sargassum ) enhanced DOC release when enriched with CO2 . DOC fluxes shifted from production in the 1‐d incubations to consumption in the 19‐d experiment under light conditions, suggesting an important role of bacteria in DOC balances. The results suggest that rising CO2 (and ocean acidification) will continue to intensify space competition in favor of the macroalgae, potentially exacerbating reef degradation and ecological phase shifts from coral to macroalgal dominance.